City Branding and Policy Legitimation in Urban Public Space Planning: A Systematic Literature Review with Reflections on the Case of Makassar - Nur Nisa SH; Rusmanhadi Takbir; Sahade Sahade (PINISI Discretion Review, 2026)
This study explores the relationship between city branding and policy legitimacy in the context of urban public space planning through a Systematic Literature Review (SLR) employing the PRISMA method. The study integrates perspectives from marketing management and public policy to capture the complexity of urban governance. By analyzing 27 articles published in Scopus- and SINTA-indexed journals (2020–2025), the research identifies four major themes: (1) legitimacy and inclusivity in place branding; (2) governance and stakeholder participation; (3) policy implementation in the regulation of street vendors and public space management; and (4) government communication and public trust. A reflective analysis of the case of Makassar (2025–2026) demonstrates a relocation–transformative approach based on the concept of a “creative ecosystem,” integrating city branding strategies with the economic empowerment of street vendors. The findings reveal an inherent tension between the aesthetic imperatives of city branding and socio-economic justice in policy implementation. This study proposes an integrative framework, termed the “City Branding–Policy Legitimacy Nexus,” as a theoretical contribution that bridges urban marketing dimensions with public policy processes in urban governance. The study recommends strengthening substantive stakeholder participation, fostering transparent two-way communication, and integrating community leadership into place branding strategies to achieve legitimate and sustainable policy outcomes.